Prediabetes and Associated Risk Factors among Undergraduate Medical Students in Bangladesh (KYAMC Journal, 2024)
Background: Early detection and timely intervention of prediabetes is an important first step in preventing the disease. Objectives: To assess the prediabetes and associated risk factors in medical students of Bangladesh. Materials and Methods: A cross-sectional study was done among 252 medical students of Shaheed Ziaur Rahman Medical College, Bogura. Data related to demography with some behavioral factors, anthropometry, blood pressure, fasting plasma glucose, family history of hypertension (HTN) and diabetes mellitus (DM) were collected. Prediabetes was assessed by the American Diabetes Association (ADA) and World Health Organization (WHO) criteria. Results: The proportion of prediabetes was 13% according to ADA and 1.6% according to WHO respectively. Students with a positive family history of hypertension (HTN) had more prediabetes compared to those who didn’t have. None of the demographic factors, family history of DM or HTN, exercise and obesity were related between prediabetic and normal students, though prediabetic students had more proportion of family history of HTN. Conclusion: Prediabetes is proportionately high among students with positive family history of HTN. We recommend a regular checking of fasting plasma glucose of medical students with special attention to those who have a strong positive family history of DM and HTN.KYAMC Journal Volume: 15, No: 01, April 2024: 20-24.